IMPROVING EFL STUDENTS' WRITING SKILLS THROUGH A GENRE-BASED APPROACH IN SECONDARY SCHOOL CLASSROOM CONTEXTS: A MIXED-METHOD STUDY - Cut Marlini; Zaki Al Fuad (Sensei International Journal of Education and Linguistic, 2024)
Writing is one of the most demanding skills for students learning English as a foreign language because it requires control of content, organization, vocabulary, grammar, mechanics, and genre conventions. Many students can produce sentences but still struggle to organize ideas into coherent texts that meet communicative purposes. This study aims to examine the effectiveness of a genre-based approach in improving students' writing skills and to explore how students experience genre-based writing instruction in secondary English as a foreign language classrooms. The study employed a mixed-method design using a quasi-experimental pretest-posttest control group approach supported by classroom observations, student interviews, reflective journals, and document analysis. The participants were 72 Grade X students divided into an experimental group and a control group. The experimental group received genre-based writing instruction through four stages: building knowledge of the field, modelling and deconstructing the text, joint construction, and independent construction. The control group received conventional writing instruction. Quantitative data were analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, normalized gain scores, and effect size analysis, while qualitative data were analyzed thematically. The findings showed that the experimental group achieved significantly higher writing improvement than the control group. Students improved in content development, text organization, vocabulary use, language control, mechanics, and genre awareness. The study concludes that a genre-based approach can improve EFL students' writing skills when instruction explicitly scaffolds text structure, linguistic features, audience awareness, and purposeful writing practice.